Clinical profile of the patients presenting with laryngeal and hypopharyngeal carcinoma: an institution based retrospective study - Jyoti, Deep; ., Arti; ., Kunzes; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: In India the overall incidence of cancer is low. However the cancers of head and neck have high incidence like that of larynx and pharynx. Methods: This is a retrospective study conducted in the department of ENT, SMGS Hospital, GMC Jammu, for a period of 3 years from June 2016 to March 2019. 112 patients with cancer of larynx and hypopharynx were included in the study. Results: The male to female ratio in the present study was 9:1. Mean age of presentation of the patients was 57.9±4.6 years. Hoarseness was the overall the most common complaint of the patients presenting with malignancy of larynx and hypopharynx (80.35%), followed by the complaint of dysphagia (68.7%). Smoking and alcohol consumption was the most common risk factor associated. 78 (69.6%) had primary malignancy of larynx and 34 (30.4%) had primary malignancy arising from hypopharynx. Most common site of presentation for laryngeal cancer was supraglottis (56/78) while pyriform sinus was the most common site to be involved in hypopharynx (24/34). 76 out of 112 patients (67.8%) presented with neck nodes. 41% of the patients presented in stage III and 32.14% patients presented in stage IV malignancy. Conclusions: Malignant laryngeal and hypopharyngeal cancers are presented in late stages when management options become limited and survival of the patients fall significantly. Awareness of the symptoms developing due to laryngeal and hypopharyngeal cancer is necessary so that people can recognize the developing cancers in earliest stages.